PARADIGMA THOMAS KUHN: REVOLUSI ILMU PENGETAHUAN DAN PENDIDIKAN - Fia Alifah Putri; Wahyu Iskandar (Universitas Islam Negeri Sumatera Utara, 2020)
Authority will be implied by scientific progress marked by the victory of each new paradigm, which is